Identification and characterization of genes influencingwssvdisease resistance in giant tiger shrimp (penaeus monodon) using a transcriptomicsapproach / Farhana Mohd Ghani - Farhana , Mohd Ghani (2020)
The giant tiger shrimp (Penaeus monodon) is one of the most extensively farmed crustacean species in the world. The emergence of diseases such as the white spot syndrome virus has however become a threat to the shrimp industry. Although there have been various studies utilizing RNA-Seq, more efforts are needed to further understand the molecular mechanisms of host-virus interaction in P. monodon. The effect of the WSSV infection on host gene expression in the haemocytes, hepatopancreas and muscle of P. monodon was investigated using Illumina HiSeq 2000. The RNA-Seq of cDNA libraries was developed from survived WSSV-challenged shrimp as well as from normal healthy shrimp as controls. A comparison of the transcriptome data of the two groups showed 2644 host genes to be significantly up-regulated and 2194 genes significantly down-regulated as a result of the infection with WSSV. Among the differentially expressed genes, this study reports the first discovered HMGB, TNFSF and c-Jun in P. monodon as new potential candidate genes for further investigation for the development of potential disease resistance markers. This study also provided valuable information on the differential expression of giant tiger shrimp genes following WSSV infection that will help to improve understanding of host-virus interactions in this species by using 22 genes related to immune response that have been identified from transcriptome data obtained in this study. An over expression of few genes including Toll protein, C-type lectin, HMGB, Kazal-type serine proteinase inhibitor 4, haemocyte kazal-type proteinase inhibitor, caspase, penaeidin, crustin, c-Jun protein, HHAP and TNF gene were observed in the present study. In addition, a total of 36,857 and 28,527 SNPs from transcriptome of survived WSSV-challenged and control shrimp were discovered respectively after 12 days post WSSV challenge, with 95.8 % markers successfully genotyped. Furthermore, 18 SNPs candidate gene markers for WSSV resistance were also identified in the present study. These markers include caspase, lectin, C-type lectin, heat shock proteins, chromosome-associated kinesin gene, haemocyanin and actin. These markers will be useful to assist stock improvement in the giant tiger shrimp by marker assisted selection (MAS).